2012
DOI: 10.4103/0019-5049.100815
|View full text |Cite
|
Sign up to set email alerts
|

Randomized crossover comparison of the laryngeal mask airway classic with i-gel laryngeal mask airway in the management of difficult airway in post burn neck contracture patients

Abstract: Purpose:The objective of the study was to compare the performance of i-gel supraglottic airway with cLMA in difficult airway management in post burn neck contracture patients and assess the feasibility of i-gel use for emergency airway management in difficult airway situation with reduced neck movement and limited mouth opening.Methods:Prospective, crossover, randomized controlled trial was performed amongst forty eight post burn neck contracture patients with limited mouth opening and neck movement. i-gel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…1 and Table 1), five of which were crossover studies [29,39,41,42,44]. All participants underwent elective surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and Table 1), five of which were crossover studies [29,39,41,42,44]. All participants underwent elective surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen RCTs included paralysed participants. Two RCTs included patients with anticipated or simulated difficult airways [39,41]. The RCTs recruited relatively few participants and were conducted at single centres using different protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I-gel has a thermoplastic cuff with a soft pliable consistency, and no inflation is necessary (Fig.3). Compatibility with perilaryngeal tissues and stability after application are the advantages of this technique [8]. Using I-gel compared to LMA, Singh et al in terms of ventilation time, airway leakage pressure, and fiberoptic view, They reported significantly greater success with I-gel than with LMA [9].…”
Section: Sheridan Et Al Utilized Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…Similarly Trivedi et al and Chauhan et al found i-gel airway was easier to insert with less attempt when compared to PLMA. 9,12,16,17 Das et al had observed higher number of manipulations to insert LMA than i-gel. 18 In our study device was placed in first attempt in 88% patients of group i-gel compared to 64% of group LMA.…”
Section: -13mentioning
confidence: 99%